Hukuman dalam Pendidikan : Studi Komparatif Pemikiran Abdullah Nasih ‘Ulwan dan B.F. Skinner - Ahmad Minan Zuhri (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2017)
This study is based on the phenomenon of the cases number of punishment  abuse in education. Punishment has become a favorite treatment chosen by teachers to control students, though not all educators choose it becomes habit. A discussion of punishment in order to educate the students, actually has been discussed several prominent Muslims and the West Islamic education  Abdullah Nashih 'Ulwan, and  the leaders of Western education for example B.F. Skinner. The education of the two figures, the authors tried to find out his thoughts about punishment in education. Furthermore, the authors compare these thoughts to determine the location of the similarities and differences, as well as the benefits and drawbacks. The results of this research are: 1) The idea of punishment in education according to Abd. Nasih 'Ulwan more emphasis on the moral requirements, while Skinner put more emphasis on human behavior; 2) Abd. Nashih 'Ulwan and Skinner do not agree with the punishment. The difference lies in the application of punishment in education. If Abd. Nashih 'Ulwan apply affectionate and gentle, while Skinner apply the principle of prudence. Keywords: Punishment in education, Abdullah Nashih 'Ulwan, B.F. Skinner